Shirin Ebadi and Gloria Steinem on Perspective as Key to Addressing Violence. Issue 2 (December 2016) - Gupta, Ruchira
This piece is based on conversations the author had with Gloria Steinem and Shirin Ebadi over the years; and explores the concept of stayagraha in the backdrop of the feminist movement, terrorism and state sponsored violence. It draws out Gloria's understanding of stayagraha and non-violence, and is an attempt at understanding the psyche which has sustained Ebadi's non-violent struggle for peace and human rights in Iran all through these years, despite the vitriolic attacks on her by the state.